Analisis Faktor Determinan Return on Asset pada Bank BUMN yang Terdaftar di Bursa Efek Indonesia - Radiman; Jufrizen; Muhammad Shareza Hafiz; Maya Sari (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2019)
This study aims to analyze the effect of Non-Performing Loans (NPLs), Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR), simultaneously on Return on Assets (ROA) on BUMN Banks listed on the Indonesia Stock Exchange either partially and simultaneously. The research approach used in this study uses an associative approach. This research was conducted at the Indonesia Stock Exchange (IDX) specifically Bank BUMN listed on the Indonesia Stock Exchange (IDX). The population used in this study was state-owned Bank companies listed on the Indonesia Stock Exchange (IDX) which amounted to 4 companies. Based on the sample withdrawal criteria above, a research sample of 4 BUMN bank companies was obtained. The type of data used is documentary data, which are research data in the form of financial statements owned by state-owned banks listed on the Indonesia Stock Exchange. Data analysis techniques are used to test the effect of Non-Performing Loans (NPLs), Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR) to Return on Assets (ROA) either partially or simultaneously is multiple linear regression. The results showed that partially Non Performing Loans (NPL) and Capital Adequacy Ratio (CAR) had a negative and not significant effect on Return on Assets. Partially, Loan to Deposit Ratio (LDR) has a negative and significant effect on Return on Assets. And simultaneously, Non Performing Loans, Capital Adequacy Ratio and Loan to Deposit Ratio have a significant effect on Return on Assets (ROA) at State-Owned Banks listed on the Indonesia Stock Exchange.